نقد روجيه جارودي للحضارة الغربية - سواكر, سعاد (University of Eloued-جامعة الوادي, 2022)
"الملخص: هذه الدراسة المعنونة بــــ: نقد روجيه جارودي للحضارة الغربية، وكان الاشكال الرئيسي الذي حاولت الإجابة عنه فيها هو لماذا نقد روجيه جارودي الحضارة الغربية ؟وما هي المجالات والقضايا التي انتقدها ؟ وللإجابة عن هذا التساؤل قمت بتقسيم الدراسة إلي أربعة مباحث: جاء المبحث الأول بعنوان روجيه جارودي والحضارة الغربية اندرج تحته مطلبين في الأول التعريف بروجيه جارودي والثاني للحضارة الغربية وفي المبحث الثاني نقد روجيه جارودي الديني ورؤيته الكونية في الغرب. وفي المبحث الثالث مطلبين أيضا: نقده للجانب السياسي وحوار الحضارات والمبحث الرابع نقد الحياة الاجتماعية والاقتصادية في الغرب ومن أهم النتائج المتوصل إليها من هذه الدراسة أن جارودي نقد الحضارة الغربية من جانب الفرد لأنه سبب كل تميزات غربية وسماها حضارة البعد الواحد . - أنها لم تكن حضارة أصيلة بل قامت على أنقاض حضارتي اليونان والرومان . - الحضارة الغربية تقوم على الفصل بين العلم والحكمة أي بين الوسائل والغايات . وكان نقد جارودي للحضارة الغربية نقد دقيقا . "" Abstract This study entitled under Roger Garaudy's criticism of Western civilization. Itbasicallytry to answer why Roger Garaudy criticize some western issues .To answer these questions ;idemy research into four chapter. The first chapter, Roger Garaudy and western civilization that that subdivided into two rubrics; who is Roger Garaudy then what is the western civilization? the second chapter, therelegious criticism and universal view to western life Chaperthree, whichdevided into two rubrics; criticising the politic side then the dialogue of civilization. The last chapter, thecriticising of Roger Garaudy the social and economical Life of west. The most important findings that we have reached are: Roger Garaudy critiqued the western life from one side-the individual- considering him the cause of distinctions The western civilization wasn't an original but rather than founded on the ruins of Greece and Romans. The western civilization is based on the separation between science and wisdom (means and wisdom) Roger Garaudy criticism of Western civilization was exact and accurate. "
مذكرة ماستر
Keywords: روجيه جارودي - الرؤية الكونية - الحضارة الغربية; Roger Garaudy - Vision cosmique - Civilisation occidentale